ANALISIS KESALAHAN MAGNITUDO FRF SISTEM SDOF DENGAN METODE SINYAL SWEPT-SINE DALAM SPAN FREKUENSI 0-50 HZ - Asmara Yanto; Reztu Illahi (Situs resmi ITP Press, 2014)
In this paper, analysis of error of FRF (Frequency Response Function) magnitude of Single Degree of Freedom (SDOF) system using swept-sine signals has been simulated. The used swept-sine signals are linear swept-sine, S111 swept-sine and S535 swept-sine signals. In numerical simulations have been done the analysis of dynamic magnification function of the system with aim to predict the minimum swept time (stimulus duration) in the linear swept-sine signal method, the S111 swept-sine signal method, and the S535 swept-sine signal method, which can yield an accurate the FRF’s magnitude of the SDOF systems. Here, the SDOF systems were varied in the 0-50 Hz of measurement frequency span with 0.5% and 1% of damping ratio. The swept-sine signal stimulus durations were varied from 1 s to 10 s. From the analysis it can be concluded that by using the linear swept-sine signal method need to stimulate a system about 7 s if the system’s resonant frequency be around mid-span 0-50 Hz of measurement frequency span. If the system’s resonance frequency is not be around mid-span 0-50 Hz of measurement frequency span, then by using this method required a longer stimulus duration to obtain an accurate the FRF’s magnitude. While using the S111 swept-sine signal and S535 swept-sine signal methods, an accurate FRF’s magnitude can be obtained through stimulus more quickly, in which the S111 swept-sine signal method with about 3 s stimulus and the S535 swept-sine signal method with about 2 s stimulus, if the system’s resonance frequency is closer to the final of 0-50 Hz frequency span.